Role and regulation of FOXO3a: new insights into breast cancer therapy - Mei, Wenqiu; Mei, Bingyin; Chang, Jing; Liu, Yifei; Zhou, Yanhong; Zhu, Ni; Hu, Meichun (Frontiers in Pharmacology, 2024)
Breast cancer is the most common malignancy in the world, particularly affecting female cancer patients. Enhancing the therapeutic strategies for breast cancer necessitates identifying molecular drug targets that effectively eliminate tumor cells. One of these prominent targets is the forkhead and O3a class (FOXO3a), a member of the forkhead transcription factor subfamily. FOXO3a plays a pivotal role in various cellular processes, including apoptosis, proliferation, cell cycle regulation, and drug resistance. It acts as a tumor suppressor in multiple cancer types, although its specific role in cancer remains unclear. Moreover, FOXO3a shows promise as a potential marker for tumor diagnosis and prognosis in breast cancer patients. In addition, it is actively influenced by common anti-breast cancer drugs like paclitaxel, simvastatin, and gefitinib. In breast cancer, the regulation of FOXO3a involves intricate networks, encompassing post-translational modification post-translational regulation by non-coding RNA (ncRNA) and protein-protein interaction. The specific mechanism of FOXO3a in breast cancer urgently requires further investigation. This review aims to systematically elucidate the role of FOXO3a in breast cancer. Additionally, it reviews the interaction of FOXO3a and its upstream and downstream signaling pathway-related molecules to uncover potential therapeutic drugs and related regulatory factors for breast cancer treatment by regulating FOXO3a.